IPTEKS APLIKASI SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH PROVINSI SULAWESI UTARA - Watulingas, Patricia; Tangkuman, Steven (Universitas Sam Ratulangi, 2018)
The system in government agencies is very important, in this case regional financial management is realized in the form of a SIMDA (Regional Management Information System) financial application. This system is a simple system for processing data, processing, obtaining, compiling, and storing to produce strategic information. The benefits obtained by the regional government by using the SIMDA regional financial application system are data that has been inputted does not need to be input repeatedly, and if the data inputted back will appear automatically. In the office of the BAPPEDA Regional Management Information System (SIMDA) working on developing to make SIMDA applications related to development, the capacity of local governments in accordance with applicable laws and regulations. To help make SIMDA develop there must be a training effort given so that SIMDA can run efficiently and effectively.Keywords: Financial SIMDA, Financial data management